The influence of uncertain expectations on Chinese rural residents’ consumer behavior decisions: Theoretical analysis and empirical test - Han, Lina; Liu, Xiaofei; Ma, Shusheng (Frontiers in Psychology, 2023)
Economic uncertainty will result in consumers’ unstable environment expectations, thus affecting household consumption decisions. The paper established a consumption model though using the cointegration theory and ECM model, and used the annual data from 2002 to 2021 to examine the influence of uncertain expectations on the consumption behavior of rural residents in China. The research results show that consumers’ income, consumption, consumption habits liquidity constraints and precautionary savings jointly produce the feelings of uncertainty, which will lead to rural consumers’ uncertain expectations. Uncertain expectations will not only lead to rural residents the prudent consumption behavior of residents, but also lead to the lack of confidence of residents, forming phased consumption characteristics. Combining the results of the empirical analysis, this paper gives suggestions to promote rural consumption from the perspective of increasing rural residents’ income, reforming the income distribution system, improving the rural financial system, and reinforcing the construction of rural consumption infrastructure.